ZnO recovered from spent alkaline batteries as antimicrobial additive for waterborne paints - López, Guillermo Pablo (2022)
Biocides are employed to prevent biodeterioration in waterborne paints. In the present study, we used zinc oxide nanoparticles (obtained from spent alkaline batteries) as biocide for indoor waterborne paint at 1.5% of the total solid content in paint. Two different zinc oxides synthesized from spent alkaline batteries, which showed photocatalyst activity, were employed as an antimicrobial agents. After leaching the anode of alkaline batteries, zinc was precipitated from the leachate liquor by introducing oxalic acid (O-ZnO) or sodium carbonate (C-ZnO). The antimicrobial properties of the prepared oxides were tested against Staphylococcus aureus (bacteria), Chaetomium globosum, and Aspergillus fumigatus (fungi) using agar well diffusion method. C-ZnO inhibited the growth of all the strains studied and presented enhanced activity than O-ZnO. The better performance as antimicrobial agent of C-ZnO compared to O-ZnO was attributed to its lower crystallite size, higher amount of oxygen monovacancies, and to its lower band gap energy. The oxide with the best performance in antimicrobial activity, C-ZnO, was employed for the formulation of waterborne acrylic paints. It was observed that 1.5% C-ZnO improved the antifungal properties and antibacterial properties compared to the control sample.